(untitled) (GUB Journal of Science and Engineering, 2020)
Launch based water vessel transportation has been growing in Bangladesh as an easier and cheaper transportation system. The shipping liners are introducing more launches in different routes as the growing demands of passengers in spite of having much difficulties with respect to uncertainty. However, this trade sector is facing imbalance in terms of profits in several service categories but they have to fight with uncertainties, a common issue faced by the liner operators. In this paper, we develop a mathematical model for the launch vessel operators to compare the profit considering different scenarios which give a broad idea about meeting the customer’s demand over time, and maximize their profit by considering different stochastic parameters. It is necessary to make decision about building launches as per demand categories, and also to maximize the profit. We show how scenario-based stochastic optimization could be applied in this perspective and discuss some solving techniques with modification as required. Finally, we conduct a numerical case study to evaluate the value of the stochastic scenario-based model over some uncertain issues according to the model. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 6(1), Dec 2019 P 46-53